Pengembangan Strategi Pembelajaran PJBL Dengan Menggunakan Model Morrison Pada Mata Pelajaran Al-Qur’an Hadist di Kelas 10 - Fajar, Azra; Jasiah (STAI Tebing Tinggi Deli, 2025)
This research provides an explanation of the project-based learning strategy which focuses on students so that the teacher does not teach in one direction. The purpose of this research is to improve the quality of learning in the classroom and increase student participation. The method used is development, namely the morrison model with several stages such as identification of instructional problems, task analysis, determination of learning objectives, learning strategy design, and evaluation & revision. The data collection techniques in this article are observation, interviews, documentation, and questionnaires. The data analysis technique used in this article is quantitative descriptive analysis. The results obtained in this article are that the project-based learning strategy based on mind mapping using the morrison model has proven effective in helping teachers to increase student participation in the learning process. This can be supported by student responses that show criteria that are “good” so learning with pjbl strategies using morrison models in addition to increasing the active involvement of students learning morrison models can also help teachers in designing learning so that learning becomes more meaningful.